Blattaria of Colombia: List and distribution of genera - Vélez, Andrés; Wolff, Marta; Gutiérrez, Esteban (Zootaxa, 2006)
Few scientists have dedicated themselves to the study of Colombia’s cockroach diversity. As a result, there are large gaps in the taxonomic knowledge of Colombian cockroach fauna that make species identification difficult and little information is available on their geographic distribution. Therefore, a taxonomic study of the suborder Blattaria was undertaken by examining the literature and studying specimens available in the country’s main entomological collections. A list of genera with their respective distribution in the various biogeographic regions was obtained. Two thousand, one hundred and forty six adult specimens, distributed in 4 families, 15 subfamilies, and 47 genera were examined and identified. The material examined comes from localities belonging to 31 of the Colombian territory’s 32 departments. Distribution data were obtained for 50 genera in seven biogeographic provinces, mainly in the North Andean and Chocó-Magdalena provinces. Seven genera are presented as new records for Colombia: Buboblatta, Cahita, Cariblatta, Euthlastoblatta, Litopeltis, Macrophyllodromia and Nahublattella. The total number of cockroach genera in Colombia is raised to 61.